Reduction in the incidence of invasive pneumococcal disease after general vaccination with 7-valent pneumococcal conjugate vaccine in Germany - Rückinger, Simon; van der Linden, Mark; Reinert, Ralf René; von Kries, Rüdiger; Burckhardt, Florian; Siedler, Anette (Vaccine, 2009)
General vaccination with the 7-valent pneumococcal conjugate vaccine was recommended in Germany in July 2006 for all children <2 years. The proportion of reported invasive pneumococcal disease (IPD) caused by vaccine serotypes before vaccine introduction was considerably lower than in the US. We report data from nationwide surveillance of IPD in children with two reporting sources, pediatric hospitals and microbiological laboratories in Germany. Incidence rates with regard to age groups and pneumococcal serotypes are based on capture recapture estimates combining the two reporting sources. Between July 1, 1997 and June 30, 2003, 2680 cases (an average 447 yearly cases) of IPD were observed in children <16 years in Germany compared to 223 cases between July 1, 2007 and June 30, 2008. A significant reduction in overall incidence (4/100,000–3.2/100,000) was attributed to significant reductions in children younger than 2 years (20.0/100,000–11.0/100,000). While the incidence of all serotypes included in the vaccine was reduced in the age group <2 years, the incidence of non-vaccine serotypes remained stable. These data show a first success of the pneumococcal vaccination program in Germany. Further changes in incidence and serotype distribution of IPD are subject to future surveillance.